Environmental regulation of a global pollution externality in a bilateral trade framework: The case of global warming, China and the US - Johnson Gwatipedza; Edward B. Barbier (Kiel Institute for the World Economy (IfW), 2013)
Bilateral trade and capital flows have increased substantially between the United States and China yielding economic gains to both countries. However, these beneficial bilateral relations also bring about global environmental consequences including greenhouse gas emissions. We develop a footloose capital model of international trade between the North (United States) and the South (China) in the presence of a global pollution externality. Each country's share of global pollution depends on its share of world capital. We show that, if the disutility of pollution in the United States is high, there will be pressure on the US to raise environmental regulations on industry. Capital will move to China. Because the increased pollution in China has global effects, the US may not benefit from the environmental restrictions and a joint regulation of pollution by both parties may be a preferred outcome. We also show that the implementation of differential control policies by the parties may also be optimal.
Keywords: D43; Q54; F18; 330; global pollution externality; agglomeration; environmental regulation; global warming; greenhouse gas emissions